Comparison of oseltamivir and α-galactosylceramide for reducing disease and transmission in pigs infected with 2009 H1N1 pandemic influenza virus - Madrid, Darling Melany de C.; Gu, Weihong; Artiaga, Bianca L.; Yang, Guan; Loeb, Julia; Hawkins, Ian K.; Castleman, William L.; Lednicky, John A.; Richt, Jürgen A.; Driver, John P. (Frontiers in Veterinary Science, 2022)
Influenza virus infections are a major cause of respiratory disease in humans. Neuraminidase inhibitors (NAIs) are the primary antiviral medication used to treat ongoing influenza infections. However, NAIs are not always effective for controlling virus shedding and lung inflammation. Other concerns are the emergence of NAI-resistant virus strains and the risk of side effects, which are occasionally severe. Consequently, additional anti-influenza therapies to replace or combine with NAIs are desirable. Here, we compared the efficacy of the NAI oseltamivir with the invariant natural killer T (iNKT) cell superagonist, α-galactosylceramide (α-GalCer), which induces innate immune responses that inhibit influenza virus replication in mouse models. We show that oseltamivir reduced lung lesions and lowered virus titers in the upper respiratory tract of pigs infected with A/California/04/2009 (CA04) pandemic H1N1pdm09. It also reduced virus transmission to influenza-naïve contact pigs. In contrast, α-GalCer had no impact on virus replication, lung disease, or virus transmission, even when used in combination with oseltamivir. This is significant as iNKT-cell therapy has been studied as an approach for treating humans with influenza.